Juridical Review of Crowdfunding Service System Through Technology-Based Stock Offering - Rachmad Abduh (International Journal Reglement & Society (IJRS), 2023)
The process of globalization in the financial system and developments in the field of financial information technology have created a financial system that is very complex, dynamic and interrelated among financial sub-sectors both in terms of products and institutions. This is also the case in the financial institution sector, which used to be aimed at helping economically weak people who need funds but on the other hand do not have the material to be used as collateral to help their business. In the sector of financial service institutions, one of the institutions born out of technological developments is financial technology (financial technology/fintech) or financial technology. Thanks to technological developments, various innovations were born to facilitate human relations, one of which is financial technology, or